Small Vs Mall - Venkateshwarlu, H.; Ranjani, C. V. (Indian Journal of Marketing, 2007)
The mall culture is catching up gradually in twin cities with several malls making their entry in Hyderabad retail sector. These malls have given a new dimension to shopping experience. Malls have transformed once compulsive and sober shopping into a family entertainment and as a weekend pastime. With the entire products available under one complex, offering rich and pleasant ambience, stocking and offering cornucopia of products and brands, these malls have already bagged a major chunk of existing retail market share.